STUDI DESKRIPTIF LAYANAN BIMBINGAN KARIR PADA SEKOLAH MENENGAH KEJURUAN SE-KOTA TARAKAN - Maryani, Yenni; Pribadi, Hendra; Aliyah, Urotul (Jurnal Bimbingan dan Konseling Borneo, 2019)
Problem formulation in this research is how the implementation of career guidance services implemented by teachers BK at Vocational School Tarakan City. This study aims to determine the implementation of career guidance services implemented by teachers BK at vocational high schools as Tarakan City. The type of this research is descriptive survey research. The population in this study were 8 BK teacher at Vocational High School and the sampel was 2 BK teachers using random sampling. Methods of data collection using questionnaires and interviews. Data analysis technique in this research is percentage analysis. The results showed that the implementation of career guidance services in Vocational High School, reaching 85,55%. This means that implementation of career services program is in accordance with the provisions and mechanisms that have been set, so the school, by looking at aspects of planning, organizing, implementation, evaluation and follow-up. Keywords : Implementation of Career Guidance Services